ANALYSIS OF ENGLISH HIGH SCHOOL TEACHER MANAGEMENT AS THE IMPLEMENTATION OF CURRICULUM 2013 - Sri Supiah Cahyati; Cynantia Rachmijati; Nai Supartini (STKIP Siliwangi, 2014)
Curriculum 2013, implemented on the academic year of 2013-2014, is one of the efforts of the curriculum developer to response to challenge of today and tomorrow, the demands from the society, the development of knowledge and pedagogy, future skills, and the uprising of the negative phenomenon. In curriculum 2013 there exist several built-in aspects in the curriculum management. They are: teachers, books, students, and supervising. The objective of this study is to analyze the teachers’ role in terms of their effort and readiness towards curriculum 2013. English subject in curriculum 2013 clearly showing that the teachers’ authority is smaller, their competence is sufficient, the workload is heavier, while the teaching-learning process is not really effective. This shows that the teachers and the implementation still needs time and supports from the stakeholders.Keywords: curriculum 2013, teachers’ management, English teacher, high school